Does Energy Poverty Reduce Rural Labor Wages? Evidence From China’s Rural Household Survey - Wu, Wei-ping; Zeng, Wei-kang; Gong, Si-wen; Chen, Zi-gui (Frontiers in Energy Research, 2021)
Eliminating energy poverty is helpful to get rid of the vicious circle between the lack of adequate and affordable energy services and low income in rural areas. We deconstruct energy poverty into extensive energy poverty and intensive energy poverty, and analyze the net effect and its heterogeneity of energy poverty on rural labor wages with micrometric methods, as well as further investigate the impact mechanism from education effect and health effect. The results show that both extensive energy poverty and intensive energy poverty have a significant negative effect on rural workers' wages, and the marginal effect of extensive energy poverty on rural workers' wages is lower than that of intensive energy poverty. In addition, the net effect of energy poverty on rural workers' wages show labor heterogeneity and regional heterogeneity, and the inhibition effect to low skilled workers and workers with middle wage as well as in the Western region are the most obvious. Furthermore, energy poverty will limit rural workers’ access to education and damage their health, and then inhibit their productivity and wage. Our results suggest that enhancing the accessibility of energy consumption in rural areas and reducing the incidence of energy poverty are critically essential, and the implementation and optimization of energy poverty alleviation policy should give full consideration to labour force heterogeneity and regional heterogeneity.